(untitled) (Eurasian Journal of Humanities and Social Sciences, 2023)
This article discusses national values in social television advertising in various countries, in particular in the Republic of Uzbekistan, Russia and the USA. The researcher analyzes and also compares national values in these countries. As is known, any national tradition combines both universal universal values and attitudes, as well as value orientations specific to a particular national community, which allow you to perceive reality, evaluate it and act in it in accordance with traditionally established patterns of behavior